"It's annoying, confusing, and it's irritating": Lived expertise for epistemic justice and understanding inequitable accessibility. (January 2023) - Lowe, Kate; Barajas, Jesus; Coren, Chelsie
Abstract: Transportation researchers seeking to advance mobility justice often focus on understanding accessibility for structurally disadvantaged groups through quantitative assessments. In addition to these technical analyses, in this article, we argue that structurally disadvantaged populations have a wealth of lived experiences that should be valued as lived expertise in the construction of transportation knowledge both for holistic understandings of actually experienced accessibility and in alignment with epistemic justice. Through Chicago-based focus group research, we find that individualized identities and community contexts combine in complicated ways that are challenging to fully capture in aggregated models. Findings also demonstrate that knowledge of inequitable accessibility and its ties to spatial inequities and the transportation system is common based on lived experience and results in continual adaptations among majority Black and Latine low- and moderate-income participants. Beyond the pragmatic need for lived expertise to adequately illuminate individual experiences beyond aggregated quantitative accessibility models, we argue a reframing to acknowledge lived expertise is critical on normative grounds for enhancing epistemic justice in transportation discourse.